Glucose-Based Molecular Rotors as Fluorescent Inhibitors and Probes of Glycogen Phosphorylase - Mavreas, Konstantinos F.; Mamais, Michael; Papazafiri, Panagiota; Gimisis, Thanasis (Chemistry Proceedings, 2020)
In this study, (E)-2-cyano-3-(6-(dimethylamino)naphthalen-2-yl)-N-(β-d-glucopyranosyl)acrylamide, a β-d-glucopyranosyl analogue of the widely used molecular rotor julolidine, was synthesized and studied photochemically. The new compound is a fluorescent inhibitor of rabbit muscle glycogen phosphorylase with properties of a molecular rotor. Fluorescence measurements in solutions of increasing viscosity determined that the fluorescence intensity increases with the viscosity of the medium, indicating that the new compound exhibits molecular rotor characteristics. Although the compound fluoresces negligibly in an aqueous buffer solution, in the presence of increasing amounts of rabbit muscle glycogen phosphorylase, we observed an increase in fluorescence intensity, which was attributed to the formation of an inhibitor–enzyme complex. In-vitro cellular studies were also undertaken, yielding promising preliminary results for the use of the new compound as a fluorescent probe.
Keywords: fluorescent probes; glycogen phosphorylase; julolidine; molecular rotor